Effect of Light-Emitting Diodes on Different Growth Stages of Rice - Hoque, MN; Islam, MZ; Ibna Sina, ANM; Singh, S; Budha, TR (Journal of Environmental Science and Natural Resources, 2022)
Effect of red and blue light on seed germination and seedling growth were studied in rice (Oryza sativa L.). Rice seeds were germinated in dark (control) and two types of light emitting-diodes (LED): red and green in the laboratory. The photoperiod of 6 h light and 18 h dark for LEDs treatment and 24h dark treatments with 24/18 ± 2 °C day/night temperature and 78± 2 % relative humidity were maintained in the growth room. Seed germination percentage under red light increased significantly when compared with the control; however, in blue light, germination percent decreased with little difference. First leaf length, first leaf blade length, root length, seedling fresh and dry weight increased under red and blue lights in most of the varieties. Highest germination (98%), longest root (8.18 cm) and high seedling fresh weight (0.527 g) and seedling dry weight (0.061g) in BRRIdhan71 and longest leaf in BRRIdhan75, were recorded under red light. Highest germination (96%), seedling fresh weight (0.414g) and seedling dry weight (0.047g) in BRRIdhan71, longest first leaf (6.50 cm) in BRRIdhan75 and longest root (9.37 cm) in BRRIdhan87 were recorded under blue light. First leaf blade showed only positive correlation with root length (r = 0.489), whereas seedling fresh weight showed complete correlation with seedling dry weight (r =1). Response index was positive in root length, seedling fresh and dry weight under red light. First leaf blade length, seedling fresh and dry weight had the positive response index under blue light. Within the visible spectrum, varying wave lengths of red and blue light alone altered the growth and morphology of rice seedlings, and variable reactions to illumination depended on the rice varieties, necessitating further research. Environ. Sci. & Natural Resources, 13(1&2): 56-62, 2020